Pola Asuh Orang Tua Dalam Membentuk Karakter Disiplin Anak Usia 5-6 Tahun Pada Masa Pandemi COVID-19 - Nurjanah Zakiyah; Nurhikma Nurhikma; Asiyah Asiyah (As-Sibyan: Jurnal Pendidikan Anak Usia Dini, 2021)
This study aims to determine the parenting applied by parents in shaping the disciplined character of children aged 5-6 years during the covid-19 pandemic on Jalan Kebun Indah RT 05 RW 01 Kel. Sukarami district. As wide as Bengkulu City. This type of research is field qualitative and descriptive. This study uses data collection techniques through interviews, observation, and documentation. The data obtained through this method is used to facilitate data analysis, then interpreted by means of inductive thinking, namely based on special knowledge then a general solution is taken, so as to produce conclusions that can be accounted for. The results showed that the parenting applied by parents in shaping the disciplined character of children aged 5-6 years during the covid-19 pandemic on Jalan Kebun Indah RT 05 RW 01 Kel. Sukarami district. The width of Bengkulu City has been used well. This is evidenced by the child's disciplinary behavior. Although there are differences in discipline in each child. Keywords: :Parenting Parenting; Discipline Character, Children Age 5-6 Years. References Susanto, Ahmad. (2017). Pendidikan Anak Usia Dini. Bumi Aksara. Al Amin, M. N. K. (2020). Menakar Nilai Kemanfaatan dari Penangguhan Walimat Al- ‘Ursy Di Masa Darurat COVID-19 Melalui Sadd Adz-Dzari’ah. Ulumuddin: Jurnal Ilmu-Ilmu Keislaman, 10(1), 27–38. Sutranto, Andina Vita & Ari Andriyani. (2018). Positive Parenting Membangun Karakter Positif Anak. Pustaka Buku Press. Eliningsih, E. (2021). Peningkatan Kemampuan Guru Dalam Manajemen Pengelolaan Kelas Di Masa Pandemi Covid-19 Melalui Supervisi Klinis Pengawas Di SDN 15 Perawang. Nuansa Akademik: Jurnal Pembangunan Masyarakat, 6(1), 25–36. Hurlock, Elizabeth B. (2019). Perkembangan Anak (2nd ed.). Erlangga. FTT IAIN Bengkulu. (2015). Pedoman Penulisan Skripsi. FTT IAIN Bengkulu. Ghofur, A., Syarifuddin, M. A., Toyyibi, A. M., & Kurnianingsih, R. (2021). Strategi Lembaga Keuangan Syariah Menghadapi Pembiayaan Bermasalah Di Masa Pandemi COVID-19. Ulumuddin : Jurnal Ilmu-Ilmu Keislaman, 11(2), 129–142. https://doi.org/10.47200/ulumuddin.v11i2.795. Gunawan, H. (2014). Pendidikan Karakter. Alfabeta. Helmawati. (2018). Pendidikan Keluarga. Remaja Rosdakarya. Herliandry, L. D., Nurhasanah, N., Suban, M. E., & Kuswanto, H. (2020). Pembelajaran Pada Masa Pandemi Covid-19. JTP - Jurnal Teknologi Pendidikan, 22(1), 65–70. https://doi.org/10.21009/jtp.v22i1.15286. Hidayat, F., Hidayat, I., Ghofur, A., & Santoso, F. S. (2021). Penanganan Kesehatan Pasien Reaktif COVID-19 Melalui Terapi Zikir Dan Lingkungan Wawasan Pengalaman Subyektif. Ulumuddin : Jurnal Ilmu-Ilmu Keislaman, 11(1), 1–12. Bahri, Husnul. (2019). Pendidikan Islam Anak Usia Dini Peletak dasar Pendidikan Karakter. CV. Zigie Utama. Imroatun, I., Nirmala, I., Juhri, J., & Muqdamien, B. (2020). Kajian Literatur Pengasuhan Anak Usia Dini Dalam Islam. As-Sibyan: Jurnal Pendidikan Anak Usia Dini, 5(1), 57–66. Kusumawati, I. (2016). Pengembangan Karakter Siswa Raudlatul Athfal Berbasis Pendidikan Agama Islam. Aṣ-Ṣibyān: Jurnal Pendidikan Anak Usia Dini, 1(2), 139–148. Mansur. (2005). Pendidikan Anak Usia Dini dalam Islam. Pustaka Pelajar. Mastoah, I., & MS, Z. (2020). Kendala Orang Tua Dalam Mendampingi Anak Belajar Pada Masa Covid 19 Di Kota Serang. As-Sibyan: Jurnal Pendidikan Anak Usia Dini, 5(2), 121–128. Habibi, Muazar. (2015). Analisis Kebutuhan Anak Usia Dini. Deepublish. Wiyani, Novan Ardy. (2012). Bina Karakter Anak Usia Dini. Ar-Ruzz Media. Syamaun, Nurmasyithah. (2019). Dampak Pola Asuh Orang Tua & Guru Terhadap Kecenderungan Perilaku Agresif Siswa. Ar-Ruzz Media. Pandoman, A. (2020). Analisis Quietus Politik Terhadap Upaya Pemerintah Menangani Wabah Covid-19 Pasca Deklarasi Public Health Emergency Of International Concern (PHEIC). Ulumuddin: Jurnal Ilmu-Ilmu Keislaman, 10(1), 1–12. Sugiyono. (2016). Metode Penelitian kuantitatif, Kualitatif, dan R&D. Alfabeta. Tridhonanto, A. & Beranda Agency. (2014). Mengembangkan Pola Asuh Demokratis. PT Alex Media Komputindo. Trisnawati, W., & Sugito, S. (2020). Pendidikan Anak dalam Keluarga Era Covid-19. Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 5(1), 823–831. https://doi.org/10.31004/obsesi.v5i1.710.